The subject and its apparatus: are they ontological trash? - Johnston, Mark (Philosophical Studies, 2021)
The article presents the discussion on testifying the Peacocke's creativity and philosophical seriousness ethically required to be responsive to the interests of beings with a moral status imposing costs on a vast multitude of fellow travellers without the consent or compensation.